The AMA Dictionary of Business and Management - Kurian, George Thomas (Amacom, 2013)
Now students, instructors, and professionals everywhere can find clear, authoritative, explanations of more than 6,000 key business terms. Prepared by a noted encyclopedist, The AMA Dictionary of Business and Management covers a vast range of terminology from all areas of business including management, strategy, finance, human resources, economics, marketing, sales, insurance, and international business. The book explains accounting rules, legal terminology, slang and buzzwords, acronyms, management theories, historical figures, economic concepts, performance metrics, and more--all the crucial ideas that have transformed business practices and management science in the past 25 years. In addition to concise definitions, this indispensable reference includes longer entries for ideas needing more elaborate explanations, as well as a pronunciation guide for difficult words, special sections on usage, and a thesaurus of related words. While quick definitions abound online, The AMA Dictionary of Business and Management supplies the depth and clarity lacking in most "webinitions." And it includes thousands of technical terms omitted from even premier unabridged dictionaries. From Abilene paradox to zero-based budgeting, this is an essential resource for anyone serious about business.